More and more students, especially those from middle-income households, are using private tutoring - Adrian Hille; C. Katharina Spieß; Mila Staneva (DIW Economic Bulletin, 2016)
Private tutoring is playing an increasingly significant role in the education of many teenagers and children: In 2013, a total of 18 percent of students at the secondary level (approximately ages 10-17) worked with paid tutors; among students at the primary level (approximately ages 6-10), this figure stood at six percent. In the period between 2009 and 2013, an average of 47 percent of 17-year-old respondents indicated that they had received tutoring at least once in the course of their school careers-roughly 20 percentage points more than what had been reported around 15 years earlier, as the present calculations show. Although households with above-average incomes engaged the services of paid tutors the most frequently of any group, discrepancies in usage among the various socioeconomic groups have started to fade: An increasing number of students from families with below-average incomes are also working with tutors, though this share remains lower than those of other groups.
Keywords: I24; J13; J24; 330; tutoring; education inequality; socio-economic differences; time trends